(untitled) (General Practice, 2021)
Introduction. Acute stroke is the second leading cause of death and the third leading cause of disability in the world. The main goal of the medical treatment is to provide the patient with thrombolytic therapy within 4.5 hours from symptom onset. The majority of patients experience first symptoms outside of health facilities, so the recognition of the symptoms, by the people who are present, is of great importance. Severe strokes, using an ambulance, and younger age coincide with decreased pre-hospital delay. Objective. We aimed to show how long is the pre-hospital delay of the patients with stroke symptoms and how it affects the patient`s treatment. Method. The research is a cross-sectional study of the ER, Belgrade, from 1.1.2015. to 31.12.2018. taking into account patients diagnosed with a stroke, suspected stroke, or TIA. Pre-hospital delay is a time from symptoms onset to the moment of seeing the physician. The patients were divided into three groups according to the delay time: up until 3h, 3-24h, and more than 24h. Statistical data processing was performed in SPSS 11 program, and statistical significance was defined at level p<0,05. Results. 119 participants took part in the study. Their average age was 65.53 ± 14.24, 46.22% were males, and 53.78% females. In the first three hours from the onset of the symptoms 44.54% of the patients arrived in the ER, 31.93% in 3-24h, and 23.53% arrived after 24h. Conclusion. More than half of the patients come to ER in time when thrombolytic therapy is no longer effective.